Implementation Of Capital Punishment In The Corruption Criminal Acts Law From A Human Rights Perspective - Wahyoe Hidayat; Desty Anggie Mustika; Ande Aditya Iman Ferrary (Universitas Ibn Khaldun Bogor, 2026)
This thesis analyzes the implementation of capital punishment for the crime of corruption, specifically the embezzlement of social aid funds during a disaster, from a human rights perspective. The research is motivated by the massive phenomenon of corruption, which systematically deprives people of their basic rights, thus creating an urgency to provide a proportional legal response. The research method used is normative legal research, with a statute approach and a case study approach. The main data sources were obtained from legal regulations, such as Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes, as well as international human rights instruments. The analysis was further strengthened by studying relevant court decisions in corruption cases related to social assistance. Our study reveals that the corruption of social aid during times of disaster constitutes an extraordinary crime, one that directly inflicts suffering and infringes upon people's right to life. Article 2, Paragraph (2) of the Anti-Corruption Law establishes a firm legal foundation for the death penalty, framing it as a measure to protect human rights from this systemic threat. From the standpoint of criminal jurisprudence, this penalty is consistent with retributive theory, which seeks proportional retribution, as well as utilitarian theory, which focuses on delivering the strongest possible deterrent to discourage future offenses. This study concludes that capital punishment for corruptors of social aid during a disaster is not a violation of human rights, but rather a manifestation of the highest form of human rights protection. The right to life of the corruptor cannot be prioritized over the right to life, the right to food, and the right to welfare of the millions of citizens who have become victims. Therefore, the state is obligated to consistently and firmly impose maximum criminal sanctions, including the death penalty, as a concrete form of enforcing justice and protecting the human rights of all Indonesian people.